BASES OF VALUATION IN GERMAN CORPORATE BALANCE SHEETS. - Kosiol, E. (The Accounting Review, 1937)
This article focuses on bases of valuation in German corporate balance sheets. Acquisition or production cost is prescribed as the maximum value for all fixed assets. The language of the present German Commercial Code is unequivocal on this point. By "acquisition cost" is meant the amount of actual expenditures on the fixed asset up to the moment when it becomes ready for use in operations. Besides the net purchase price this form of cost includes all direct overhead expenses, for instance, transportation costs, insurance premiums, import duties, commissions, cartage expenses, and installation costs. The bookkeeping technique of recording depreciation, in view of the great variety of practices, is not regulated by law, and must, therefore, be determined individually according to the principles of good accounting. The principle of minimum value applies to all current assets. The previous enumeration, as current assets, of securities and other assets which are not permanently required for the business conduct of the company, as well as of merchandise and the company's own shares, is now replaced by reference to the corresponding section of the classification ordinance.